Learning Amid The Covid-19 Pandemic: What is The Attitude Towards Science of Middle School Students? - Setiawan, Heri; Suhandi, Andi; Rochintaniawati, Diana (Jurnal Pendidikan MIPA, 2021)
This article aims to find out the attitude toward science of students during online learning in the midst of the Covid-19 pandemic which is reviewed based on the TOSRA indicator. The method used in this study is a descriptive method. The sample used in the study amounted to 55 students of MTs Negeri 2 Bolaang Mongondow. The study was conducted by spreading the 4 point science attitude scale instrument to students as many as 20 statement items. The results showed that the indicators enjoyment of science lessons, leisure interest in science, further study in the field of science, and career interest in science got an average score of 77.38 in the excellent category, 74.54 in the high category, 68.36 in the high category, and 65.72 in the high category. While the overall average value at 71.38 is in the high category. Thus, it can be concluded that the attitude toward science of students in the midst of the covid-19 pandemic is in a good category. The results also showed that the TOSRA indicator is effectively used to measure students' attitudes toward science.Keyword: learning in a time of pandemic, distance learning, attitude toward science. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp188-197